Engineering mechanics. dynamics - Meriam, J. L.; Kraige, L. G.; Bolton, J. N. (John Wiley & Sons, 2016)
Known for its accuracy, clarity, and dependability, this work has provided a solid foundation of mechanics principles for over 60 years. To help students build necessary visualisation and problem-solving skills, the text strongly emphasises drawing free-body diagrams - one of the most important skills needed to solve mechanics problems.